Exploring the subjective and objective characteristics affecting the frequency of human-nature interactions in urban green spaces: a case study from Finland - Poturalska, Anita; Ala-Hulkko, Terhi; Artell, Janne; Juutinen, Artti; Kangas, Katja (Springer Nature, 2026)
Green urban and peri-urban spaces are important sites for human-nature interactions, providing countless ecosystem services to support the wellbeing of urban populations. In an era of rapid urbanization, understanding human-nature interactions requires considering both subjective, user-specific perspectives and the objective measures of environmental and infrastructural features of these green spaces. In this case study we explore how different groups of characteristics impact the number of visits and, consequently, human-nature interactions frequency in urban and peri-urban spaces across three Finnish cities: Espoo, Kuopio, and Jyväskylä. We used Public Participatory Geographic Information Systems survey data of which respondents marked the green urban and peri-urban spaces they visit annually. A panel generalized linear modelling approach was used to analyze the roles of four groups of subjective and objective characteristics on the visit frequency, including: the socio-demographic background of survey respondents; the cultural ecosystem services they consume; the perceived accessibility characteristics of the marked locations; and the presence of objectively measured environmental and infrastructure features of these locations. Our findings underline the importance of perceived accessibility and availability of infrastructure for more frequent interactions with nature. Additionally, they emphasize the need of urban residents for access to biodiverse green spaces within closer proximity to their homes. Ensuring the availability of green spaces and preserving their ability to provide ecosystem services is essential for maintaining the well-being of urban populations now and in the future.
Keywords: green urban and peri-urban green spaces; nature interactions; visit frequency; public participatory geographic information systems; panel generalized linear models